POP UP BOOK ILLUSTRATION DESIGN AS A LEARNING EDUCATIONAL MEDIA FOR STUDENTS OF SEMESTA 2 SMP SEMARANG - Aulia, Dyah Septi Anisatul; Prameswari, Nadia Sigi (LPPM Univ. Ibn Khaldun Bogor, 2025)
Pop up book design research as a learning education media conducted at SMP Semesta 2 Semarang aims to describe the design of learning media as a new innovation to increase student learning motivation. The type of research used is research and development by designing everything needed in the research process. Pop up book learning media is made using a mixture of manual and digital techniques with a finishing process using the photoshop application. Based on the ongoing research, the results of the study showed that pop up book design can increase student interest in participating in learning activities as well as become a new perspective in the world of education.